2022
DOI: 10.3390/plants11101367
|View full text |Cite
|
Sign up to set email alerts
|

Cold Stress, Freezing Adaptation, Varietal Susceptibility of Olea europaea L.: A Review

Abstract: Olive (Olea europaea L.) is an evergreen xerophytic tree characterizing vegetative landscape and historical-cultural identity of the Mediterranean Basin. More than 2600 cultivars constitute the rich genetic patrimony of the species cultivated in approximately 60 countries. As a subtropical species, the olive tree is quite sensitive to low temperatures, and air temperature is the most critical environmental factor limiting olive tree growth and production. In this present review, we explored the detrimental eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 147 publications
(257 reference statements)
1
19
0
Order By: Relevance
“…In their study, sorghum plants kept at 2, 5, and 8˚C for 8 days exhibited visual CI damage after removal from chilling temperatures. In agreement to this study, Petruccelli et al [24] reported that chilling temperatures of 7.5 to 12.5°C not show chilling injury symptoms in olive (Olea europaea L.). Nonetheless, metabolic processes like respiration and photosynthesis are significantly reduced, thus resulting in decreased production.…”
Section: Discussionsupporting
confidence: 91%
“…In their study, sorghum plants kept at 2, 5, and 8˚C for 8 days exhibited visual CI damage after removal from chilling temperatures. In agreement to this study, Petruccelli et al [24] reported that chilling temperatures of 7.5 to 12.5°C not show chilling injury symptoms in olive (Olea europaea L.). Nonetheless, metabolic processes like respiration and photosynthesis are significantly reduced, thus resulting in decreased production.…”
Section: Discussionsupporting
confidence: 91%
“…Cold stress severely affects plants, leading to a decline in plant development, growth, and germination, and causing a substantial reduction in crop yield [ 32 , 33 , 34 ]. However, critical/chilling temperatures ranging from 7.5 to 12.5 °C may strongly impede the metabolic processes including photosynthesis and respiration in plants [ 35 ]. The oil palm is sensitive to low-temperature stress, which may inhibit the growth of oil palm seedlings [ 3 , 4 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extreme environmental conditions of high-altitude region (i.e., low oxygen concentration, high ultraviolet (UV) radiation, extreme temperature, salinity, etc.) might affect plant growth and distribution [ 19 ]. Yet, how medicinal plants in response to high-altitude environmental stresses is not sufficiently studied [ 17 ].…”
Section: Environmental Stresses Of Natural Plants At High Altitudementioning
confidence: 99%